Kepercayaan Diri Dan Kemampuan Komunikasi: Overall Effect Size - Hukom, Julham (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to synthesize empirical findings on the impact of self-confidence on students' communication skills through a meta-analytic approach. A total of twelve studies published within the last five years were analyzed using a random effects model. The results showed that self-confidence has a significant impact on students' communication skills, with a combined effect size of 0.72 and a standard error of 0.028. This finding falls into the high-effect category. However, the high heterogeneity across studies (I² = 89%) indicates substantial contextual variation. These results provide strong evidence that self-confidence is a critical internal factor that should be nurtured to enhance students’ communication skills effectively. The findings also offer a scientific foundation for developing learning strategies and educational interventions that focus more on strengthening students’ psychological readiness.